THE EFFECT OF ENTERPRISE RESOURCE PLANNING IMPLEMENTATION, ACCOUNTING CONSERVATISM, AND GOOD CORPORATE GOVERNANCE ON EARNINGS QUALITY: AN EMPIRICAL STUDY OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2016–2022) - evy steelyana (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2026)
Purpose – This study examines the effects of Enterprise Resource Planning (ERP) implementation, accounting conservatism, and Good Corporate Governance (GCG) mechanisms on earnings quality among companies listed on the Indonesia Stock Exchange (IDX) during the period 2016–2022. The study is motivated by increasing concerns regarding financial reporting quality during periods of economic uncertainty, particularly before and during the COVID-19 pandemic. Research Method – A quantitative research approach was employed using secondary data obtained from audited annual reports of companies operating in the food and beverage, cement, banking, and insurance sectors. Based on purposive sampling criteria, 40 companies were selected, resulting in 280 firm-year observations. Following data screening procedures, 202 valid observations were retained for regression analysis. The data were analyzed using descriptive statistics, classical assumption tests, and multiple regression analysis. Findings – The findings reveal that Enterprise Resource Planning (ERP) implementation, accounting conservatism, audit committees, and independent commissioners have positive and significant effects on earnings quality. These results indicate that integrated information systems, prudent accounting practices, and effective corporate governance mechanisms play important roles in improving the reliability and credibility of financial reporting. Implication – This study contributes to the literature by integrating information systems, accounting practices, and corporate governance perspectives within a single framework to explain earnings quality in an emerging market context. The findings provide practical implications for managers, regulators, and investors seeking to enhance earnings quality through digital transformation, conservative accounting practices, and stronger governance mechanisms.